2021
DOI: 10.1111/epi.16793
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy‐reported cause of death in a population‐based cohort of sudden unexpected death in epilepsy

Abstract: Objective Sudden unexpected death in epilepsy (SUDEP) is a diagnosis of exclusion; the definition includes individuals with epilepsy who die suddenly without an identifiable toxicological or anatomical cause of death. Limited data suggest underidentification of SUDEP as the cause of death on death certificates. Here, we evaluate the autopsy‐reported cause of death in a population‐based cohort of SUDEP cases. Methods Case summaries of forensic autopsies conducted in Ontario, Canada between January 2014 and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 10 publications
1
20
0
3
Order By: Relevance
“…Most of the included studies exploited NLP techniques to identify—and discriminate between—patients based on their documented clinical history and conditions 16–30 . The process often entailed classifying patient reports or interviews into predefined categories based on the prominent differences in textual features.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the included studies exploited NLP techniques to identify—and discriminate between—patients based on their documented clinical history and conditions 16–30 . The process often entailed classifying patient reports or interviews into predefined categories based on the prominent differences in textual features.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies explored the role of NLP in identifying patients in the context of sudden unexplained death in epilepsy (SUDEP) 25,27 . Barbour and colleagues developed rule‐based NLP algorithms that could distinguish patients at risk of SUDEP based on SUDEP risk variables in physician notes, including generalized tonic–clonic seizure (GTCS), refractory epilepsy, and potential or previous epilepsy surgery candidacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For SUDEP cases with alternative CODs, undetermined or unascertained was often reported by Forensic pathologists, with epilepsy included as contributing factor or mentioned in case comments. Neurologists, on the other hand, tend to classify these cases as definite SUDEP plus [ 36 ]. Communication between epileptologists and pathologists, and a standard COD classification are needed for epilepsy‐associated death investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, SUDEP does not directly lead to death, however, it can give rise to accidental falls and trauma as well as drowning. The prevalence of SUDEP is underestimated (13). Previous studies have demonstrated that only ∼30% of SUDEP cases are reported as SUDEP, seizure, or epilepsy (4,14).…”
Section: Introductionmentioning
confidence: 99%